(untitled) (AYUSHDHARA, 2017)
Urinary calculi is one of the most common and painful urological disorder of the urinary tract affecting 10-12 % of the population. It is characterized by frequent micturition, intermittent pain occasionally radiates to flanks, sweating and restlessness during the pain. Most of the patients taking allopathic medicine but calculi was not expel or crushed from the urinary tract. Endoscopic procedures such as ureterostomy, percutaneous nephrolithiotomy and extracorporeal shockwave lithotripsy or other surgical procedures is the treatment of choice in case of ureteric calculi in the conventional system. Non-invasive and safe study had designed for the management of this entity. In the present study, An Ayurvedic intervention Chandraprabha Vati (500 mg ) and Swetparpati (250 mg) along with decoction of natural herbs 30 ml twice in a day for 90 days used for ureteric calculi. The response to the treatment is encouraging by symptoms relief and through lower abdomen ultrasonography (USG). Ureteric calculi has expel from the tract through this management.